Collaborative governance in the child-friendly school program at Krian 1 Junior High School - Ramadhani, Mutiara Nabilah; Hertati, Diana (Universitas Muhammadiyah Malang, 2026)
Kabupaten Sidoarjo, has the highest number of cases of violence against children in East Java. CFS is implemented in collaboration with various actors because the prevention and handling of cases of violence against children requires cooperation with various parties. The purpose of this study is to identify, describe, and analyze the collaboration process in Collaborative Governance in the realization of Child Friendly School at Krian 1 Junior High School Sidoarjo. This is reinforced by the lack of studies on collaborative governance in child-friendly school from a cultural transformation perspective in Kabupaten Sidoarjo. The collaboration was carried out by DP3AKB Kabupaten Sidoarjo, Krian 1 Junior High School , and PT Karya Bintang Mandiri. The research method used was descriptive qualitative, which described the analysis based on the collaborative governance theory according to Ansell and Gash, namely starting condition, facilitative leadership, institutional design, and collaborative processes. The results obtained from this study indicate that the CFS collaboration process at Krian 1 Junior High School has been running well, although it is not yet ideal according to the four criteria of collaboration according to Ansell and Gash. Obstacles arise from the lack of transparency of other companies in Sidoarjo that have not reported their CSR assistance to the DP3AKB of Kabupaten Sidoarjo. In the process of implementing the collaboration, each actor has carried out their respective roles, enabling the implementation of CFS at Krian 1 Junior High School to proceed in accordance with the initial objectives. Kabupaten Sidoarjo memiliki jumlah kasus kekerasan terhadap anak tertinggi di Jawa Timur. SRA dilaksanakan bekerja sama dengan berbagai pihak karena pencegahan dan penanganan kasus kekerasan terhadap anak memerlukan kerja sama dengan berbagai pihak. Tujuan penelitian ini adalah untuk mengidentifikasi, mendeskripsikan, dan menganalisis proses kolaborasi dalam Tata Kelola Kolaboratif dalam implementasi Sekolah Ramah Anak di SMP Negeri 1 Krian Sidoarjo. Hal ini didukung oleh minimnya penelitian tentang tata kelola kolaboratif dalam sekolah ramah anak dari perspektif transformasi budaya di Kabupaten Sidoarjo. Kolaborasi dilakukan oleh DP3AKB Kabupaten Sidoarjo, SMPN 1 Krian, dan PT Karya Bintang Mandiri. Metode penelitian yang digunakan adalah deskriptif kualitatif, yang menggambarkan analisis berdasarkan teori Collaborative Governance menurut Ansell dan Gash, yaitu kondisi awal, kepemimpinan fasilitatif, desain kelembagaan, dan proses kolaboratif. Hasil penelitian ini menunjukkan bahwa proses kolaborasi SRA di SMPN 1 Krian telah berjalan dengan baik, meskipun belum ideal menurut empat kriteria kolaborasi menurut Ansell dan Gash. Hambatan muncul akibat kurangnya transparansi dari perusahaan-perusahaan lain di Sidoarjo yang belum melaporkan bantuan CSR mereka kepada DP3AKB Kabupaten Sidoarjo. Dalam proses implementasi kolaborasi, setiap pihak telah melaksanakan peran masing-masing, sehingga implementasi SRA di SMPN 1 Krian dapat berjalan sesuai dengan tujuan awal.